Characterization and Effect of Processing on Parvalbumin Content in Indonesian Shortfin Eel (Anguilla Bicolor-bicolor) - Mahardika, Vania; Nurilmala, Mala; Nurjanah, Nurjanah; Pertiwi, Rizsa Mustika; Nugraha, Roni (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2023)
Indonesian shortfin eel (Anguilla bicolor bicolor) is a high economic value fish and a high nutritional content. However, their utilization can be limited because of hypersensitivity cases in individuals allergic to fish. This study aimed to determine the characteristics of the fish major allergenic protein, parvalbumin in different parts of the eel fillet and the effects of boiling technique on the content of this protein. The samples were boiled with 100 mL of water in an Erlenmeyer flask at 95°C for 10 min. The eel fillet was divided into three parts: the front, middle, and rear part of the body. Protein profiles from each part were identified using sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Bradford assays. Parvalbumin was further purified by ammonium sulfate precipitation. The concentration of protein in the different parts of the eel was not significantly different, whereas the processing treatments (meat with water (F1 extract) and meat without water (F2 extract)) affected protein concentration. Eel meat contained proteins with molecular weights ranging from 10 to 186 kDa. Parvalbumins are highly water-soluble, as their content was reduced in the fillet, but were observed at a high concentration in the water after boiling. Parvalbumins of eel were purified by ammonium sulfate 70-90% with high purity. Interestingly, two different bands were observed in SDS-PAGE, suggesting the presence of a protein variant. The molecular weight of parvalbumin obtained from purification ranged from 10 to 11 kDa, similar to that of other fish.